Beleza Natural : marketing strategies for empowering social change - Chernev, Alexander; Kilibarda, Vasilia (London : Kellogg School of Management, 2016)
This case features an entrepreneur striving to rapidly grow a successful chain of hair salons that serve women with afro hair. After doubling from 13 to 26 salons across Brazil in 2014, the founders' expansion plan called for 120 Beleza Natural salons and R$1 billion in sales by 2018. CEO and cofounder Leila Velez is considering various fundamental marketing strategies to catalyze growth: Should Beleza launch a new mass-media campaign, increase promotional discounts, expand its target market to serve men, broaden its service offerings, streamline processes to reduce wait times, expand distribution channels, or franchise? Students assume the role of Velez and are asked to recommend which growth strategy would be their top priority. In doing so, they are required to evaluate how these strategies pertain to the company's business model and value proposition. They are also challenged to consider what a brand is and what makes a strong service brand in order to verify if their strategies are consistent with Beleza's brand. The teaching note outlines a framework for developing or evaluating a business model as well as developing strategies for managing growth. The case is accompanied by a series of video interviews with Velez that support case preparation, in-class discussion, and key learning points.
Originally Published InChernev, A., & Kilibarda, V. (2016). Beleza Natural: Marketing Strategies for Empowering Social Change. 5-116-002. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Beleza Natural (Brazil) -- Case studies; Marketing -- Management -- Case studies